Sustainable waste management and recycling. proceedings of the international conference organised by the Concrete and Masonry Research Group and held at Kingston University, London on 14-15 September 2004 - Limbachiya, Mukesh C.; Roberts, J. J. (Thomas Telford, 2004)
Contains proceedings of the International Conference, by the Concrete and Masonry Research Group, held at Kingston University. This work emphasises on increasing recycling and promoting more sustainable waste management practices, greater co-ordination between the public, and all concerned with the management of waste and reusable materials.